Life cycle cost-effectiveness estimation and optimization method for satellite - ZHAO Jianyu, WANG Jingyan, CHENG Zhuo, JIAO Jian, CHENG Yao (Zhihui kongzhi yu fangzhen)
In order to design satellite with low cost and high effectiveness, an optimization method of life cycle cost-effectiveness for satellites is proposed in this paper. Since most satellites are unrepairable and their performances experience degradation in orbit, a life cycle effectiveness model based on ADC model is constructed. Then, a multidimensional parameter cost model is proposed to estimate the satellite cost. Finally, an optimization model and the solution method are developed by synthesizing the life cycle effectiveness model and the multidimensional parameter cost model based on CAIV. A remote sensing satellite is adopted to demonstrate the proposed method, the result suggests that this method could optimize the performance, reliability and weight indicators of satellite system, which might be applied for project design demonstration, task management, and life cycle cost control of satellites.